Pengaruh Mengelola Emosi Terhadap Komitmen Organisasi Pengurus UKK KSR-PMI UIN Antasari Banjarmasin - Setiawan, Muhammad Sofyan; Komalasari, Shanty; Musfichin, Musfichin (Jurnal Al-Husna, 2022)
There are many causes that affect the organizational commitment of members, one of which is how a person is able to manage his emotions when organizing. This research uses a quantitative approach. Sampling used purposive sampling technique and the number of respondents in this study were 50 students, namely 95% of the total population. The measuring instrument used in managing emotions refers to the theory of Goleman and Hud, while the organizational commitment variable refers to the theory of Allen and Mayer which was compiled. The data analysis used in this study was simple linear regression analysis. The results of the analysis show that the level of managing emotions is in the medium category and the level of organizational commitment is in the medium category. Based on the results of simple linear regression analysis shows that there is a significant effect between managing emotions on organizational commitment with an R square value of 0.562 and a significance value of p = 0.000 <0.05. This means that there is an influence between managing emotions on organizational commitment with a percentage of 56.2% while the remaining 43.8% is influenced by other factors not disclosed in this study.